2020
DOI: 10.1051/0004-6361/201937083
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of large-amplitude oscillations in flux rope solar prominences

Abstract: Context. Large-amplitude oscillations (LAOs) of the solar prominences are very spectacular but poorly understood phenomena. These motions have amplitudes larger than 10 km s −1 and can be triggered by the external perturbations, e.g., Moreton or EIT waves. Aims. Our aim is to analyze the properties of large-amplitude oscillations using realistic prominence models and the triggering mechanism by external disturbances. Methods. We perform time-dependent numerical simulations of LAOs using a magnetic flux rope mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 106 publications
3
33
0
Order By: Relevance
“…This model suggests that the period is defined by the radius of curvature of the magnetic field (see also Roberts 2019, for another description of the model). The following studies, based on the analytical calculations or the 2D and 3D simulations, confirmed that the pendulum model describes quite well the periods of longitudinal oscillations under typical prominence conditions (e.g., Luna et al , 2016Zhou et al 2018;Zhang et al 2019;Liakh et al 2020;Fan 2020). Zhou et al (2018) found a systematic discrepancy of some 10% with respect to the pendulum model.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This model suggests that the period is defined by the radius of curvature of the magnetic field (see also Roberts 2019, for another description of the model). The following studies, based on the analytical calculations or the 2D and 3D simulations, confirmed that the pendulum model describes quite well the periods of longitudinal oscillations under typical prominence conditions (e.g., Luna et al , 2016Zhou et al 2018;Zhang et al 2019;Liakh et al 2020;Fan 2020). Zhou et al (2018) found a systematic discrepancy of some 10% with respect to the pendulum model.…”
Section: Introductionsupporting
confidence: 53%
“…These numerical simulations showed significant damping which might be partly contributed by numerical diffusivity. Liakh et al (2020) studied the convergence of a 2.5D experiment of LALOs excited in a magnetic flux rope. The authors performed an experiment with a spatial resolution of 60 km and compared it to the one with a spatial resolution of 240 km.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the particularly large amplitude oscillations are reserved for those filaments in the vicinity of a flare, wherein the filaments are subjected to the expanding magnetic pressure bubble of the nearby eruption. The amplitudes of such dynamics are also significantly larger than those at the smaller scales, with velocities and displacements in the region of 30 -100 km s −1 and 110 Mm, respectively (e.g., Luna & Karpen 2012;Luna et al 2014;Liakh et al 2020). More recently, similarly large-scale and correlated mass motions occurring in the lead-up to a filament eruption have been added to the conditions for global flux rope stability (e.g., Bi et al 2014;Reva et al 2017;Jenkins et al 2018Jenkins et al , 2019Fan 2020), alongside the more commonly-considered stability conditions (e.g., torus/kink instability, breakout reconnection, tether cutting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation shows that mass drainage reduces the damping time considerably in one strong perturbation (Zhang et al 2013). Recent numerical simulations have shed light on the nature of large-amplitude longitudinal oscillations (e.g., Terradas et al 2015;Zhou et al 2018;Adrover-González & Terradas 2020;Liakh et al 2020Liakh et al , 2021.…”
Section: Introductionmentioning
confidence: 99%